The Influence of Project Based Learning on Students' Learning Outcomes and Creative Thinking Ability - Aryani, Ima; Chimam, Shella Latifah (Universitas Muhammadiyah Surakarta, 2025)
The main issue addressed in this study is the limited creative thinking skills among students. During classroom activities, teachers often employ learning models that are less effective, causing students to become passive and struggle to grasp the material presented. This study seeks to examine how the implementation of the Project-Based Learning (PjBL) model affects students' academic performance and creative thinking abilities in seventh-grade biology instruction. A quantitative descriptive design was adopted, employing a quasi-experimental method with a randomized pretest–posttest control group structure. The research population consisted of 51 students. Data were collected through pretest and posttest instruments, as well as observation sheets assessing creative thinking and project performance. The findings revealed that the average score achieved by the experimental group (75.96) exceeded that of the control group (68.40). In addition, learners who engaged in the experimental treatment exhibited a very high level of creative thinking ability, whereas those in the control group demonstrated a good level. These findings suggest that applying the Project-Based Learning approach contributes significantly to improving students' academic performance and enhancing their creative thinking competence.